OVERSEAS EXPERIENCE OF HEALTH SAVING – A VIEW IN THE PAST - Donchenko, V. (World of Medicine and Biology, 2018)
The article is devoted to the detailed analysis of foreign experience on implementing health-saving technologies into practice while training medical experts. The view that the main objective of a medical expert is prevention of diseases among the population has been substantiated.
Keywords: health-saving technologies; healthy lifestyle